DINAMIKA EROSI TANAH DAN KRISIS EKONOMI-ERA REFORMASI DI DAERAH ALIRAN SUNGAI SERAYU HULU - Rustanto, Andry (UI Scholars Hub, 2019)
A large-scale horticulture crops practices in addition to land use / land cover changes in the upper Serayu Hulu catchment has been reported as the most responsible factor of the sedimentation acceleration in the downstream hydropower plant reservoir. This acceleration may become a serious problem for the hydropower plant because it would shorten the reservoir lifespan from the initial estimation. The problem could be further worst if the soil conservation practices application is still limited and land use / land cover changes that tend to increase run-off keep on progress. One of such situation in contrast has been occurred during 1997 - 1998 when financial crisis hit the country followed by the succession of the political regime. Due to the above situation, land use / land cover changes in the period expanded into higher elevation and slope. On the other hand, financial crisis has limited the attention of the horticulture crop farmers in applying soil conservation practices. This paper shows that those two factors together with climatic condition have increase the soil detachment in the hillslope before and after the country financial crisis and political regime succession in 1997 – 1998 by more than 100%. However, the soil detachment rate was then decreasing after some years even though still higher than before 1997